2022
DOI: 10.5455/njcm.20201215020144
|View full text |Cite
|
Sign up to set email alerts
|

Menopause Related Health Problems and Quality of Life of Menopausal Women from Urban Slums of Western Maharashtra: An Observational Study

Abstract: Introduction: During menopause, women may experience vasomotor, psychosocial, physical, as well as sexual dysfunction. Studies on menopausal issues and health demand priority in the Indian scenario due to the growing population of menopausal women as a result of their increased life expectancy. Materials& Methods: A cross-sectional study was conducted using a predesigned, structured questionnaire based on socio-demographic variables and menopausal symptoms as per the MEN-QOL questionnaire and adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A study done by Anandkumar et al . [ 17 ] among urban women reported 45 years as the mean age of the participants. A study done by Dąbrowska-Galas et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study done by Anandkumar et al . [ 17 ] among urban women reported 45 years as the mean age of the participants. A study done by Dąbrowska-Galas et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] reported similar findings while Anandkumar et al . [ 17 ] and Karma et al . [ 21 ] reported poor memory; Ganapathy et al .…”
Section: Discussionmentioning
confidence: 99%
“…Considering all the above aspect, the investigator concluded that menopausal women need educational teaching program on perimenopausal care and to study the program's effectiveness on the level of depression and quality of life symptom, which occurs in 80% of the cases. [3][4][5][6]…”
Section: Introductionmentioning
confidence: 99%